Catholic Bishops in the United States church leadership in the third millennium - Fichter, Stephen J. 1967-; Gaunt, Thomas P.; Hoegeman, Catherine; Perl, Paul M. (New York, NY Oxford University Press, 2019)
During the past 25 years the Church has gone from Pope John Paul II to Benedict XVI to Pope Francis, and the Catholic Church in the United States, along with its bishops, are dramatically different. The bishops of the United States have had their leadership tested by the sex abuse scandals, the movement of Catholics from the Northeast and Midwest to the South and West, and the arrival of more Catholic immigrants than they have seen in a century along with the ongoing decline in the number of priests and sisters serving the Catholic community. This text provides a unique and comprehensive view of who the bishops are, where they are from, and how they are leading the Church in the United States in the era of Pope Francis.
Previously issued in print: 2019. - Includes bibliographical references and index. - Description based on online resource; title from home page (viewed on January 14, 2019)
Keywords: Catholic Church -- Bishops -- United States; Catholic Church -- History -- 21st century -- United States; Christian Leadership -- Catholic Church; Catholic Church ; United States ; Bishops; Catholic Church ; United States ; History ; 21st century; Christian leadership ; Catholic Church